2018
DOI: 10.1002/cncr.31216
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal cancer beliefs, knowledge, and screening among Filipino, Hmong, and Korean Americans

Abstract: Knowledge regarding the causes of CRC and its prevention among Filipino, Hmong, and Korean individuals is low. However, health care access, not knowledge or beliefs, was found to be a key determinant of CRC screening. Cancer 2018;124:1552-9. © 2018 American Cancer Society.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
26
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(31 citation statements)
references
References 28 publications
2
26
0
Order By: Relevance
“…People who had insurance coverage for CRC screening had better knowledge, most probably because their insurance agent could explain the details about CRC screening and its procedures to them, meaning their perception of CRC and its screening was improved. Subsequently, they were more willing to participate in the CRCSP [ 8 , 10 ]. Insurance coverage reduces the psychological and financial burdens related to obtaining an expensive CRC screening test, leading to better attitudes and practices towards CRC and CRC screening [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…People who had insurance coverage for CRC screening had better knowledge, most probably because their insurance agent could explain the details about CRC screening and its procedures to them, meaning their perception of CRC and its screening was improved. Subsequently, they were more willing to participate in the CRCSP [ 8 , 10 ]. Insurance coverage reduces the psychological and financial burdens related to obtaining an expensive CRC screening test, leading to better attitudes and practices towards CRC and CRC screening [ 8 , 10 ].…”
Section: Discussionmentioning
confidence: 99%
“…Similar CRC screening programs (CRCSP) have been promoted in other countries [ 6 , 7 ], however the participation rates have been low [ 5 , 6 , 7 ]. Evidence has shown that poor knowledge affects attitudes and practices of participation in CRC [ 8 , 9 , 10 , 11 ]. Studies were conducted to understand factors associated with participation rates in CRC screening [ 12 , 13 ].…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Despite the high incidence and death rates from CRC for KAs, their CRC screening rates (32.7%) remain significantly lower than those of non-Latino Whites (57.7%) and subgroups (46.8%) of Asian Americans, including Chinese (81.3%), Japanese (59.8%), and Vietnamese (47.8%), as well as the national target (i.e., 70.5%) specified by Healthy People 2020 (Jackson, Oman, Patel, & Vega, 2016; Tran et al, 2018; U.S. Department of Health and Human Services, 2010).…”
Section: Introductionmentioning
confidence: 99%